Methodical techniques for lighting and aesthetic adjustment of plastic forms of design objects in the interior under artificial lighting. - Цой, Микола Павлович (Theory and practice of design, 2019)
The article deals with the technique of light technical geometric modeling of the system of the most important characteristics of plasticity of a form for visual images in the most difficult cases for practice - on frame curves of surfaces of forms of a subject environment in an interior. The method of two surfaces and the method of graphical iterations and circular auxiliary projection are analyzed. Attention is drawn to the fact that the construction of polishes, shadows and glare on the surfaces makes it possible to adjust the light and aesthetic adjustments of plastic forms in the process of their design in the environment. To create a methodology for the proper construction of orthogonal projections, studies were proposed to determine the shortest distance from point to surface, to determine the brilliant point on the surface from the point of light emission for a given observation point. It is proved that the proposed tools and methodical techniques of geometric modeling to lighting and aesthetic correction of plastic forms of objects of design in the interior in artificial lighting reveal the method of geometrical modeling of the system of basic lighting characteristics designed in the interior of modern plastic geometric shapes caused by point light. Such a tool was lacking in design-ergonomic design technology to accurately graphically illuminate the illumination of projected forms and optimally adjust their shape accordingly, including other principles and means of the laws of composition and shaping.